Epidemiology of bacteremia in young hospitalized infants in Vientiane, Laos, 2000-2011. - Anderson, M; Luangxay, K; Sisouk, K; Vorlasan, L; Soumphonphakdy, B; Sengmouang, V; Chansamouth, V; Phommasone, K; Van Dyke, R; Chong, E; Dance, D; Phetsouvanh, R; et al. (2014)
As data about the causes of neonatal sepsis in low-income countries are inadequate, we reviewed the etiology and antibiotic susceptibilities of bacteremia in young infants in Laos. As Staphylococcus aureus is the leading cause of bacteremia in Lao infants, we also examined risk factors for this infection, in particular the local practice of warming mothers during the first weeks postpartum with hot coals under their beds (hot beds). Clinical and laboratory data regarding infants aged 0-60 days evaluated for sepsis within 72 h of admission to Mahosot Hospital in Vientiane, Laos, were reviewed, and 85 of 1438 (5.9%) infants' blood cultures grew a clinically significant organism. Most common were S. aureus, Escherichia coli and Klebsiella pneumoniae. Whereas no methicillin-resistant S. aureus was found, only 18% of E. coli isolates were susceptible to ampicillin. A history of sleeping on a hot bed with mother was associated with S. aureus bacteremia (odds ratio 4.8; 95% confidence interval 1.2-19.0).